Establishment of a polymerase chain reaction-based method for strain-level management of Enterococcus faecalis EF-2001 using species-specific sequences identified by whole genome sequences - Hamamoto, Hiroshi; Ogasawara, Akihiko Ano; Iwasa, Masahiro; Sekimizu, Kazuhisa (Frontiers in Microbiology, 2022)
In the development and manufacture of fermented foods, it is crucial to control and manage the bacterial species used in the products. We previously reported a complete genome sequence analysis of the Enterococcus faecalis EF-2001 strain that was used for supplements. By comparing this sequence to the publicly available complete genome sequence of E. faecalis strains, we were able to identify specific sequences of the EF-2001 strain. We designed primer sets to amplify these specific regions and performed a polymerase chain reaction (PCR). We confirmed that the DNA fragments were specifically amplified in the genome of the EF-2001 strain, but not those of other lactic acid bacteria (LABs) or strains of the same genus. Furthermore, these primers amplified DNA fragments even in genomic DNA extracted from heat-treated bacteria at 121°C and foods containing the EF-2001 strain. These results suggest that this method allows for simple and highly accurate identification of specific fermentation strains, such as LABs at the strain level, which will be useful for controlling the quality of fermented foods.